Planejando a carreira : orientação e transição para o mundo do trabalho dos psicólogos da Universidade Federal de Minas Gerais - Thiago Venturelli de Almeida (2022)
The aim of this dissertation, consisting of two studies, sought to analyze the preparatory process for leaving the university of students about to graduate in the Psychology course at the Federal University of Minas Gerais, as well as to evaluate how the transition from university to the labour market is happening. Study I investigated, from a qualitative perspective, the students' experiences in a preparatory course for leaving the university called Career Planning Seminars. Its evaluation took place through the answers of a questionnaire about the course and sought to analyze whether this intervention complied with its proposal and to understand in what way. In general, the analysis of the students' responses indicates that the proposal was successful in its objective of helping students At this moment of reflection and career planning, being characterized as a relevant and pertinent process, being highly praised, but also criticized for the time of its realization. Study II addressed, through interviews, how psychologists graduating from the Psychology course build their career paths in the first years after graduation. It sought to describe and analyze the paths of graduates from their training until the time of the research, identifying the possible factors that influenced their choices within their career paths. The results of Study II corroborate the findings of Study I regarding the need for greater preparation during the graduation for a smoother transition. The interview reports describe the difficulties faced by the graduates and how this generates feelings of anguish and despair. Consequence of the very thought of not feeling prepared at the end of the course, and not having a concrete and conscious planning for this transition. University experiences promote aspects that develop the sense of self-efficacy, such as participation in internships and activities that generate confidence, but in general, they do not encourage a commitment to think about their own formation and future professional performance. Thus, higher education constitutes a propitious moment for the development of decision-making on the professional path and the transition to the job market. To better prepare and train students about to leave the university and enter the job market, it is interesting to create spaces for reflection on academic and career paths that are implemented at different moments of formation.